Astrogenesis in the murine dentate gyrus is a life‐long and dynamic process. (22nd April 2022) - Schneider, Julia; Weigel, Johannes; Wittmann, Marie‐Theres; Svehla, Pavel; Ehrt, Sebastian; Zheng, Fang; Elmzzahi, Tarek; Karpf, Julian; Paniagua‐Herranz, Lucía; Basak, Onur; Ekici, Arif; Reis, Andre; et al.
Abstract: Astrocytes are highly abundant in the mammalian brain, and their functions are of vital importance for all aspects of development, adaption, and aging of the central nervous system (CNS). Mounting evidence indicates the important contributions of astrocytes to a wide range of neuropathies. Still, our understanding of astrocyte development significantly lags behind that of other CNS cells. We here combine immunohistochemical approaches with genetic fate‐mapping, behavioural paradigms, single‐cell transcriptomics, and in vivo two‐photon imaging, to comprehensively assess the generation and the proliferation of astrocytes in the dentate gyrus (DG) across the life span of a mouse. Astrogenesis in the DG is initiated by radial glia‐like neural stem cells giving rise to locally dividing astrocytes that enlarge the astrocyte compartment in an outside‐in‐pattern. Also in the adult DG, the vast majority of astrogenesis is mediated through the proliferation of local astrocytes. Interestingly, locally dividing astrocytes were able to adapt their proliferation to environmental and behavioral stimuli revealing an unexpected plasticity. Our study establishes astrocytes as enduring plastic elements in DG circuits, implicating a vital contribution of astrocyte dynamics to hippocampal plasticity. Synopsis: Murine dentate gyrus astrocytes derive from neural stem cells and locally divide to establish the astrocytic niche during development. Here, astrogenesis is found to persist to old age, representing a dynamic process mostly driven by local astrocyte proliferation. During postnatal development, astrocytes in the murine dentate gyrus derive from perinatal radial glia‐like neural stem cells, and locally proliferate to generate the astrocyte compartment in an outside‐in‐pattern. Dentate gyrus astrogenesis persists until adulthood and is predominantly driven by locally proliferating astrocytes. Adult astrogenesis is a dynamic process that contributes to a fixed neuron‐to‐astrocyte ratio within the adult dentate gyrus, which is preserved under pro‐neurogenic stimuli. While neurogenesis rapidly declines upon aging, astrogenesis diminishes only much later in life leading to a shift in the neuron‐to‐astrocyte ratio towards astrogenesis. Abstract : Immunohistochemical analysis combined with genetic fate‐mapping, behaviour, imaging, and single cell transcriptomics show that astrogenesis persists to old age and is responsive to environmental and behavioural stimuli.